NNLO beam functions for angularity distributions - Guido Bell; Kevin Brune; Goutam Das; Marcel Wald (Journal of High Energy Physics)
Abstract The popular class of angularity event shapes provides a wealth of information on the hadronic final-state distribution in collider events. While initially proposed for e + e − collisions, angularities have more recently attracted considerable interest as a jet substructure observable at hadron colliders. Moreover, angularities can be measured as a global event shape in deep inelastic electron-nucleon scattering (DIS), and the respective factorisation theorem contains a beam function that parametrises the collinear initial-state radiation. In the present work, we compute the quark and gluon beam functions for seven different angularities to next-to-next-to-leading order (NNLO) in the strong-coupling expansion. Our calculation is based on an automated framework that was previously developed for SCET-2 observables, and which we transfer in the current work to the generic SCET-1 case. Our results are relevant for resumming DIS angularity distributions at NNLL′ accuracy.